Business Performance Of Muslim Smes: Perceptions Of Training, Mentoring And Coaching For Aspikmas Members - Fatmah Bagis; Akhmad Darmawan (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to analyze Business Performance of Muslim SMEs: Perceptions of training, mentoring and coaching for Aspikmas members. This research is a case study at the Association of Micro, Small and Medium Enterprises (Aspikmas), especially Muslim SMEs in Purwokerto. Respondent data was obtained by using an open questionnaire filled out by 65 person Muslim SMEs. This study used data analysis techniques namely PLS (Partial Least Square) analyisis using Smart PLS 3.0. The results showed that training on business performance is not supported. The result showed that mentoring on business performance is supported. The result also showed that coaching on business performance is supported. The effect of training, mentoring and coaching on the business performance of Muslim SMEs in Purwokerto show that the R2 value of 0.614 indicates that 61.4% of the variability in the construction of business performance is influenced by these three factors. Keyword: Business performance, Perceptions of training, mentoring and coaching.